Interaction between Caregivers and Children with mild Developmental Disabilities: Study of Social Behavior in the Saint Vincentius Orphanage Foundation Merauke Branch - Noiman Derung, Teresia; Ngarawula, Bonaventura; Prianto, Budhy (International Journal of Psychosocial Rehabilitation, 2020)
The general objective of this study was to determine the interaction between caregivers and children with mental retardation at Bhakti Luhur, Merauke. The specific objective is to analyze and describe the interactions between caregivers and mildly mentally retarded children at the St. Vincentius Merauke Orphanage, to analyze and describe the factors that become internal and external impetus in the interaction between caregivers and mildly mentally retarded children who are in the St. Vincentius Orphanage Foundation Bhakti Luhur Merauke Branch. This research used a descriptive-qualitative approach. The location or place of research for this dissertation was the St. Vincentius Orphanage, Jalan Domba No.3 Rimba Jaya Village, Merauke District. The Key Informant was a servant mother as the Head of the St. Vincentius Orphanage, the Merauke Bhakti Luhur Foundation, which is fully responsible and directly involved in education, guidance, and services for children with special needs. The other key informant was the researchers themselves, because the researchers explored various sources through participant observation, in-depth observation, and in-depth interviews. Data analysis techniques followed the theory of Strauss & Corbin: opening coding, axial coding, and selective coding. The study found that interactions between caregivers and mildly mentally retarded children in St. Orphanage Vincentius Yayasan Bhakti Luhur Merauke Branch in reading activities are a continuous mutual interaction. Caregivers accompany children with mild mental retardation in reading activities carried out step by step until they can read fluently. Caregiver assistance for mildly mentally retarded children in reading activities takes longer because the children's ability to learn is slower than that of normal children, and the children also learn to adjust. Factors that encourage caregivers to interact with mildly mentally retarded children are internal factors and external factors. This study recommends further research on educational models for mildly retarded children.